The Cause and Effect of Consequences Frame on the Perception of Obesity among 35-55 Years University Female Academic Staff in Nairobi County, Kenya - Kahiga, Naomi; Mberia, Hellen; Ngula, Kyalo Wa (International Journal of Communication and Public Relation, 2020)
Purpose: To establish the cause and effect of consequences frame on the perception of obesity among 35-55 years University female academic staff in Nairobi County, Kenya. Methodology: This study applied the one-group pretest-posttest experimental design. In the one-group pretest-posttest experimental design all study participants provided with the same treatment and assessment. The researcher therefore, collected data using the pre-and posttest questionnaires. The treatment applied is Slimpossible television program season six episode one was purposively selected out of seven seasons and ninety-eight episodes covered by the Slimpossible television program. The obese females were qualified through an interview process to participate in the Slimpossible challenge, a popular weight loss television program aired by Citizen Television Network. The justification for choosing the season six episode one television program was based on assessing the media frames according to Entman (1993), where the scholar mentions the following: human interest, consequences, morality, and responsibility. Although this study is a quasi-experimental research design, the researcher attempted to use randomization to improve the validity of the pretest and posttest experimental study design. Furthermore, out of the randomly selected sample, a purposeful sample was selected for assessment based on a specific interest (Stratton, 2019). The data was analyzed using the Statistical Package for Social Sciences (SPSS) version 23.0. This study presented descriptive statistics using tables with frequencies and percentages. Secondly, the research conducted inferential statistics using several types of inferential analysis tools such as the Factor analysis (The Keiser-Meyer -Olkin (KMO) test), Pearson's correlation coefficient, and regression analysis (logical regression). Findings: The descriptive statistics shows that physical consequences, like obesity-related diseases, and psychological and social consequences significantly cause and affect the perception of obesity, except for economic consequences, where there was no relationship. Secondly, with increased social and physical consequences, the respondents were likelier to have a lower negative perception towards obese 35-55 years University female academic staff of Nairobi County than higher levels of negative perception. Therefore, the results show a statistically significant relationship between the three factors of the consequences frame, except economic consequences. Unique Contribution to Theory, Practice and Policy: In terms of contribution to theory, this study emanated from the media framing theory, where it provided consequences frame as one among five frames, mentioned by an American political scientist known as Robert Entman in 1993. Its contribution to practice, the conclusions help in recommending that bodies like the Media Council of Kenya and Kenya Union of Journalists, in conjunction with Nutritional and Dietary Consultant, should create media programmes that talk about the consequences of obesity on society and how to help 35-55 years University female academic staff suffering from obesity. They could work with UNESCO and the Ministry of Health to develop well-written communication strategies to curb obesity and advocate for better nutritional practices. The study recommends that international bodies such as the World Health Organization and the Ministry of Health -in Human Nutrition and Dietetics Unit be actively involved in developing relevant nutrition policies that address obesity cases affecting individuals.